Analysis of Blood Hemoglobin Levels Using Biosensors Based on Heme Oxygenase from Serratia marcescens - Ahmad Irvan Pratama; Aisyah Sahara; Sintia Intan Agsari (Current Biochemistry, 2020)
Hemoglobin levels are influenced by nutrition, iron conditions, and body metabolism. One of the medical disorders related to human blood, especially erythrocyte levels is anemia. This condition causes the need for effective and efficient methods of measuring blood hemoglobin levels, including in terms of cost. One alternative measurement of hemoglobin levels that can be used is the heme oxygenase-based sensor from Serratia marcescens. This study aims to develop techniques to measure blood hemoglobin levels by utilizing biological sensor based on heme oxygenase fromSerratia marcescens. The stages of the experiments include: rejuvenation and production of Serratia marcescens isolates, isolation of heme oxygenase, purification of enzymes with ammonium sulphate 45-65% and 65-85% saturation, measurement of protein content and enzyme activity, enzyme immobilization to the surface of carbon electrodes, and assay of biosensor heme oxygenase kinetics. Test of protein content and enzyme activity produces enzyme specific activity at 45-65% fraction of 0.0158 U/mg and at 65-85% fraction of 0.0069 U/mg, so the fraction to be used in biosensors is 45-65% fraction. The biosensor kinetics test results in a hemoglobin level of 12.0, 13.8, and 14.3 g/dL in blood samples A, B, and, C, while the hemoglobin level measured in a standard laboratory test is 12.0, 13.8, and 14.3 g/dL. It was concluded that the biosensors developed in this study can measure hemoglobin levels in blood samples with a precision of 0.8 and an accuracy of 96.04%.